Evaluation of relative economic value of performance traits in Sahiwal cattle - POONAM RATWAN; A K CHAKRAVARTY; MANOJ KUMAR (Indian Journal of Animal Sciences, 2022)
Estimation of economic values is essential to decide the monetary importance of traits to be incorporated in breeding programs. The present study was conducted to estimate the relative economic value of first lactation traits, viz. 305-day milk yield (305DMY), average daily milk yield (ADMY), calving to first insemination interval (CFI), days open (DO), pregnancy rate (PR) and longevity (LNG) in Sahiwal cattle. Data spanning over duration of 29 years pertaining to production, reproduction and longevity of Sahiwal cattle kept at ICAR-NDRI herd were utilized. Averages of first lactation traits, viz. 305DMY, ADMY, CFI, DO, PR and LNG were obtained as 1822.59 kg, 6.62 kg/day, 85.56 days, 150.48 days, 38.00% and 2711.95 days, respectively with lactation length of 303.02 days in Sahiwal cattle. Expenses involved for different groups of animals for five years (2012-2016) were considered for appraising relative economic values of above-mentioned performance traits. Major expenses considered were per day cost of feeding, treatment, labour and artificial insemination for each animal. Cost of production of one kg milk was calculated as ` 23.68 which was the economic value of 305DMY and ADMY. The per unit expenses for traits CFI, DO, PR and LNG were ` 156.79, 156.79, 86.65, and 141.21, respectively in Sahiwal cattle. Relative economic values were estimated as 1, 1, -6.62, -6.62, 3.66 and 5.96 for 305DMY, ADMY, CFI, DO, PR and LNG, respectively. Relative economic values estimated in the present study will be helpful for constructing selection indices for genetic progress of Sahiwal cattle.